Innovative Heavy Metal Waste Disposal System: Modular Approach for Senior Secondary Chemistry Teachers - Rai, Suresh; Kumar, Rajesh; Khatri, Dilip (SCHOOL SCIENCE, 2017)
Handling and disposal of waste generated during laboratory experiments is prime concern to school education. Most of the waste chemicals generated from laboratories are hazardous so their disposal waste must be given special consideration. This innovative disposal system guides for proper waste management and also helps in minimising the risk of exposure to maintain a safe school environment. The several experiments at school laboratory waste contain heavy metal ions. After completion of experiment the segregation and safely disposal of waste containing heavy metal ions is the main challenge. The readily available glassware was utilized to have easy, fast, cost effective and safe laboratory practice for heavy metal disposal.